2024
DOI: 10.3389/fendo.2024.1367376
|View full text |Cite
|
Sign up to set email alerts
|

Association of the systemic immuno-inflammation index, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio with diabetic microvascular complications

Jiahang Li,
Xueying Wang,
Wenjing Jia
et al.

Abstract: BackgroundThe systemic immuno-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) are widely used and have been shown to be predictive indicators of various diseases. Diabetic nephropathy (DN), retinopathy (DR), and peripheral neuropathy (DPN) are the most prominent and common microvascular complications, which have seriously negative impacts on patients, families, and society. Exploring the associations with these three indicators and diabetic microvascular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…T2DM patients with elevated NLR levels should have their potential risk to kidney function closely monitored [ 47 ]. Studies have also found that NLR is highly valuable in diagnosing diabetic retinopathy [ 48 ]. The above reports indicate that NLR, as an inflammatory marker, has positive potential applications in predicting and managing diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM patients with elevated NLR levels should have their potential risk to kidney function closely monitored [ 47 ]. Studies have also found that NLR is highly valuable in diagnosing diabetic retinopathy [ 48 ]. The above reports indicate that NLR, as an inflammatory marker, has positive potential applications in predicting and managing diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%